2020
DOI: 10.1108/mbe-01-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary paths of performance measurement and management system: the longitudinal case study of a leading SME

Abstract: Purpose The literature highlights the relevance of performance measurement and management system in small and medium enterprises (SMEs) to face the current competitive environment. However, a number of studies investigate how performance measurement and management system is effective for evolving and how contingency factors could influence this change. Newer experiences are sporadic and rarely investigated by researchers and practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 51 publications
(121 reference statements)
3
49
0
7
Order By: Relevance
“…The finding of the fourth hypothesis is in agreement with the premise of the "fit-as-mediation" which states that knowledge-related factors could determine the usage and design of specific organizational systems such as management accounting and control systems in general and PMS in particular . This is also in harmony with Sardi et al (2020aSardi et al ( , 2020b, who observed that HRM is a contributing factor in supporting the enhancement of the maturity of performance measurement and the improvement of performance management. In summary, this result suggests that knowledge-intensive companies that possess more knowledge assets place emphasis on more comprehensive PMS to capture the real contribution of their strategic knowledge resources.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The finding of the fourth hypothesis is in agreement with the premise of the "fit-as-mediation" which states that knowledge-related factors could determine the usage and design of specific organizational systems such as management accounting and control systems in general and PMS in particular . This is also in harmony with Sardi et al (2020aSardi et al ( , 2020b, who observed that HRM is a contributing factor in supporting the enhancement of the maturity of performance measurement and the improvement of performance management. In summary, this result suggests that knowledge-intensive companies that possess more knowledge assets place emphasis on more comprehensive PMS to capture the real contribution of their strategic knowledge resources.…”
Section: Discussionsupporting
confidence: 71%
“…The effective implementation of performance measurement and management systems is of critical importance to the company's success (Sardi et al, 2020a;Siti-Nabiha and Jurnali, 2020;Melnyk et al, 2014). Such systems represent a holistic, balanced and dynamic mechanism whereby the decision-making process is facilitated through a range of performance measurement practices, including collecting, elaborating and analyzing performance (Sardi et al, 2020b;Neely et al, 2001), along with performance management practices, consisting of communicating, learning and enhancing performance (Sardi et al, 2018).…”
Section: Performance Measurement Systems and Corporate Performancementioning
confidence: 99%
“…Data triangulation was achieved by using multiple sources of information [ 31 , 36 , 37 ]. Multiple resources supported the researchers to crosscheck data and verify the validity of the data obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The research used a qualitative case study methodology which favors detailed research of a specific subject [38,39]. This methodology is commonly adopted in business, social, and educational research [40]. It involves qualitative methods for describing, comparing, and evaluating different aspects of a research problem [41].…”
Section: Methodsmentioning
confidence: 99%
“…(c) Data analysis. As already used by other empirical researches [18,40], data were analyzed through:…”
mentioning
confidence: 99%